Pengaruh Penggunaan Alat Peraga Pada Pembelajaran Matematika Terhadap Hasil Belajar Siswa Ditinjau Dari Keaktifan Siswa Kelas X Smk Muhammadiyah Delanggu Tahun 2016/2017 - Sevi Adila, Melia; , Dra. Sri Sutarmi,M.Pd (2017)
This research aims to examined (1) the significant influence use of props on mathematics student learning outcomes, (2) a significant influence student activity toward mathematics student learning outcomes, (3) the interaction between the use of props and student activity toward mathematics student learning outcomes. Quantitative research with quasi-experimental design. The research population and sample are 10th grade students of SMK Muhammadiyah Delanggu. The sampling technique used cluster random sampling. The data collection instruments were a test, questioner and documentation method. The data were analyzed using two-way analysis of variance with different cells. The results of the research with α = 5% is (1) there is significant influence of use of props on mathematics student learning outcomes, (2) there is a significant influence students activity on mathematics student learning outcomes, (3) there is no interaction between the use of props with students activity towards mathematics student learning outcomes. Keywords: props, mathematics student learning outcomes, students activity.